Improving the organizational structure of Company X - Lin, Jordan C. (Animo Repository, 2023)
This action research established a formalized organizational structure within Company X, a family-owned and operated real estate firm based in Mandaluyong City, Philippines. The COVID-19 pandemic has affected businesses across all industries and the real estate industry is no exception. Despite the initial downturn experienced, the industry was able to weather the effects of the pandemic fairly better compared to other industries. This silver lining, however, does not mean that Company X was operating completely without issues. The gravity of the pandemic has led key members of Company X to choose to relocate to Taiwan, leaving only one family member behind to hold the reins of the enterprise. This has led to excessive, recurring passing around of tasks and responsibilities, which ultimately led to inefficiencies in the organization’s operations. This action research aims to address the root cause of the operational inefficiencies within Company X. Action research tools, including the first, second and third person practices, are applied throughout this research. These collaborative tools include the force-field analysis, Ishikawa Diagram, and the RACI Matrix. All these tools are applied with frequent collaboration, discussion, and co-inquiry. The first cycle of this action research focused on the definition, distribution and the implementation of new roles and responsibilities among collaborators. The second cycle, on the other hand, focused on addressing the lapses and deficiencies that have occurred during the first cycle. The study was concluded with a causal snapshot that could serve as a quick guide for change makers facing a similar situation.